Molecular Mechanisms Involving the Sonic Hedgehog Pathway in Lung Cancer Therapy: Recent Advances - Ma, Chao; Hu, Kang; Ullah, Irfan; Zheng, Qing-Kang; Zhang, Nan; Sun, Zhi-Gang (Frontiers in Oncology, 2022)
According to the latest statistics from the International Agency for Research on Cancer (IARC), lung cancer is one of the most lethal malignancies in the world, accounting for approximately 18% of all cancer-associated deaths. Yet, even with aggressive interventions for advanced lung cancer, the five-year survival rate remains low, at around 15%. The hedgehog signaling pathway is highly conserved during embryonic development and is involved in tissue homeostasis as well as organ development. However, studies have documented an increasing prevalence of aberrant activation of HH signaling in lung cancer patients, promoting malignant lung cancer progression with poor prognostic outcomes. Inhibitors targeting the HH pathway have been widely used in tumor therapy, however, they are highly associated with drug resistance. Interestingly, natural products, either alone or in combination with chemotherapy, have greatly improved overall survival outcomes for lung cancer patients by acting on the HH signaling pathway because of its unique and excellent pharmacological properties. In this review, we elucidate on the underlying molecular mechanisms through which the HH pathway promotes malignant biological behaviors in lung cancer, as well as the potential of inhibitors or natural compounds in targeting HH signaling for clinical applications in lung cancer therapy.